URGENSI PENDIDIKAN AGAMA DIKALANGAN NELAYAN PESISIR ACEH - Syibran Mulasi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
As the province with the most Muslim population in Indonesia and with the Aceh special law in carrying out Islamic law, of course, religious education becomes its necessity in the view of the Acehnese people, including the fishing community. This study aims to look at the urgency of religious education for children among Aceh's coastal fishing communities and access to religious education institutions in the village as well as the factors of children's education. This study uses a qualitative research approach with descriptive data exposure, the study was conducted in villages inhabited by fishermen scattered throughout the coastal areas of Aceh, while the informants were fishing communities, village heads and apparatus where fishermen live, panglima laot, and people who could provide information with the required data. While data collection is done by observation, interviews, and documentation. The results showed that the Acehnese fishing communities prioritized the religious education of their children, the maximum availability of religious educational institutions in the village, then several obstacles hindered the education of fishermen's children, such as economic factors, the distance to formal schools was too far, motivation to go to school, and involved in making a living with their parents